A Potential Late Stage Intermediate of Twin-Arginine Dependent Protein Translocation in Escherichia coli - Geise, Hendrik; Heidrich, Eyleen Sabine; Nikolin, Christoph Stefan; Mehner-Breitfeld, Denise; Brüser, Thomas (Frontiers in Microbiology, 2019)
The twin-arginine translocation (Tat) system transports folded proteins across membranes of prokaryotes, plant plastids, and some mitochondria. According to blue-native polyacrylamide gel electrophoresis after solubilization with digitonin, distinct interactions between the components TatA, TatB, and TatC result in two major TatBC-containing complexes in Escherichia coli that can bind protein substrates. We now report the first detection of a TatABC complex that likely represents the state at which transport occurs. This complex was initially found when the photo cross-linking amino acid p-benzoyl-l-phenylalanine (Bpa) was introduced at position I50 on the periplasmic side of the first trans-membrane domain of TatC. Cross-linking of TatCI50Bpa resulted in TatC-TatC-cross-links, indicating a close proximity to neighboring TatC in the complex. However, the new complex was not caused by cross-links but rather by non-covalent side chain interactions, as it was also detectable without UV-cross-linking or with an I50Y exchange. The new complex did not contain any detectable substrate. It was slightly upshifted relative to previously reported substrate-containing TatABC complexes. In the absence of TatA, an inactive TatBCI50Bpa complex was formed of the size of wild-type substrate-containing TatABC complexes, suggesting that TatB occupies TatA-binding sites at TatCI50Bpa. When substrate binding was abolished by point mutations, this TatBCI50Bpa complex shifted analogously to active TatABCI50Bpa complexes, indicating that a defect substrate-binding site further enhances TatB association to TatA-binding sites. Only TatA could shift the complex with an intact substrate-binding site, which explains the TatA requirement for substrate transport by TatABC systems.